Knowledge-based view in social entrepreneurship - Premadasa, M.; Amarawansha, H.; Gamage, S.; Jayawardhana, K.; Siyambalapitiya, J.; Fernando, I. (University of Jaffna, 2022)
Purpose: The knowledge-based view (KBV) of social entrepreneurship is a powerful mechanism to transform knowledge into innovations. This viewpoint of social enterprises differs from that of commercial enterprises, as typical businesses have only one bottom line such as profit, but social enterprises have three, namely: people, planet and profit. Thus, the overarching objective of this study is to recognize the knowledge based view in social enterprises. Methodology: The study followed a qualitative research paradigm and semi-structured interviews were conducted with 24 local social entrepreneurs who belong to several sectors, including service and manufacturing, across the country. Consequently, the key respondents of the study were the owner-managers or senior managers of the social enterprises in Sri Lanka. Further, to derive the sample, the study used the maximum variation sampling technique as it assists in determining the maximum variation of social enterprises in the sector. Finally, the data was analyzed thematically as it could provide reliable and insightful results. Findings: The study explored three (03) themes to recognize the knowledge-based view in social enterprises, namely: a) sources of knowledge gathering, b) knowledge dissemination, and c) knowledge integration. First, the study identified three most mentioned sources of knowledge gathering in social enterprises: i) social associations, ii) research, and iii) intuition. Second, this study identifies that social enterprises disseminate knowledge primarily through informal networks. Third, it revealed that social enterprises integrate their knowledge in terms of i) directives and ii) routines. Thus, the study explored significant differences in how social enterprises gather new knowledge, disseminate the knowledge within their organizations, and combine this new knowledge when coming up with novel initiatives. Research limitations: A limited number of social entrepreneurs were interviewed in the study. However, the sample and sampling technique were reliable enough to cover a wide range of variation within the social enterprise sector. Implications: Subsequently, the study provides valuable implications for theory, practitioners, and policymakers. First, this paper mainly contributes to the strategic management literature through the interpretation and application of a knowledge based view in a Sri Lankan social enterprise research context. It also adds to the field's ongoing discussion of developing context-specific theories for SE. Second, it provides implications for practitioners. Herein, knowledge exchange has been highlighted as one of the essentials toward the economic and social goals within social enterprises. Thus, our Findings proposed several sources that social enterprises should use to build established social enterprises. Third, the study has implications for policymakers by providing insights into how knowledge exchange lifts inventiveness and allows social enterprises to more quickly respond to environmental necessities or demands. Overall, this study contributes to the academic field of SE by emphasizing the significance of rethinking the KBV of social entrepreneurship from the perspective of developing countries.
Keywords: Knowledge-based view; Social entrepreneurship; Innovation